Randomized Control Trial Endline Data on Use of Improved Efficient Cookstoves in Mozambique - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This survey was conducted to collect endline data for a randomized control trial, two years after the introduction of the improved cookstoves in the Angonia District of Mozambique. A similar endline study was also conducted in Malawi in the district of Dedza. Angonia district in Mozambique was selected because it shares a transboundary with the Dedza district in Malawi and has similar biophysical and socioeconomic conditions. This selection was intended because the project was set out to examine how differences in policies in these two countries contributed to the adoption and use of improved cookstoves under a randomized control trial experiment.